К вопросу об уменьшении вместимости византийских грузовых кораблей в «темные века» - Сорочан, С. Б. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary Sorochan S. B. The Question of Capasity Decrease of Byzantine Cardo Ships During "Dark Ages" The stable opinion about the reduction of cargo tonnage of the ships during the «dark ages» is being discussed and preliminary judgment about much more chronological limits of this process is being put forward. This reduction can’t be explained only by the stagnation in trade. The cargo tonnage of the ships didn’t undergo any substantional changes in VII–IX centuries in comparison with for going centuries of the antic epoch in X–XIII centuries. At that period the Byzantines considered the average cargo tonnage of any ship of about 60–100 registered tons. The conclusion is apparent that the small tonnage sea vessels dominated all this time as the main source of transportation over large and even middle vessels and they performed trade according to the required volumes in the early and middle Byzantine periods.